2015
DOI: 10.1016/j.rchipe.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Caries dental y desarrollo infantil temprano. Estudio piloto

Abstract: This pilot study indicates that the severity of dental caries is correlated with early childhood development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
1
0
11
Order By: Relevance
“…As seen in other populations, dental caries in preschool-age children remains a problem, and the high percentage of S-ECC is even more worrisome, considering that if affects the quality of life and the risk of developing dental caries in permanent teeth. 14,20 According to the survey, oral hygiene habits showed that both mothers and children brushed at least 1 time a day in 68.8%, and the clinical examination yielded an O'Leary's index of 98.7%. This shows that brushing has a different effect in each individual and its frequency does not necessarily result in effective removal of biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in other populations, dental caries in preschool-age children remains a problem, and the high percentage of S-ECC is even more worrisome, considering that if affects the quality of life and the risk of developing dental caries in permanent teeth. 14,20 According to the survey, oral hygiene habits showed that both mothers and children brushed at least 1 time a day in 68.8%, and the clinical examination yielded an O'Leary's index of 98.7%. This shows that brushing has a different effect in each individual and its frequency does not necessarily result in effective removal of biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Tal como se ha visto en otras poblaciones, la caries dental en niños en edad preescolar sigue siendo un problema, y es más preocupante el porcentaje alto de CIT severa, teniendo en cuenta cómo se afecta la calidad de vida y el riesgo de desarrollar caries dental en la dentición permanente. 14,20 Los hábitos de higiene oral reportaron, a través de la encuesta, que tanto las madres como los niños se cepillaban al menos 1 vez al día en un 68,8%, y en el examen clínico se observó un índice de O'Leary del 98,7%. Esto indica que el cepillado tiene un efecto diferente en cada individuo y la frecuencia del mismo no necesariamente se ve reflejada en una remoción eficaz de la biopelícula.…”
Section: En Los 546 Niños Y Niñas Pertenecientes a Los Hogaresunclassified
“…Entendiendo que la prevención en aspectos de salud se inicia en el hogar (21) y que los problemas de salud varían de acuerdo con la edad del individuo (12) , resulta indispensable considerar la importancia de trabajar en procesos educativos preventivos desde la etapa intrauterina (22) , afirmación que se refuerza por múltiples estudios que han demostrado que la educación temprana y el establecimiento de hábitos de higiene oral son una de las mejores herramientas de control de problemas de salud a nivel sistémico y bucal.…”
Section: Discussionunclassified
“…Los preescolares con caries pierden más días de jardín infantil o colegio (Hollister y Weintraub, 1993) y consecuentemente tienen peor rendimiento escolar (Jackson et al, 2011). Además tienen una dieta deficiente que los hace propensos a la anemia (Bansal et al, 2016) y obesidad (Dos Santos Junior et al, 2014), lo cual lleva a que los niños con caries tengan alteraciones en su desarrollo físico (Acs et al, 1992) y psicomotor (Núñez et al, 2015). Asimismo, los niños con CTI tienen entre dos a cuatro veces más riesgo de tener caries en su dentición definitiva (Li y Wang, 2002) y tienen en promedio 14 dientes más con daño de caries en comparación a niños que no tuvieron caries en su dentición temporal (Jordan et al, 2016).…”
Section: Introductionunclassified